Father’s Role and Support in Fulfilling Nutrition of Children with Cancer: A Review - Fatma Zulaikha; Nur Fithriyanti Imamah; Enok Sureskiarti (Indonesian Journal of Global Health Research, 2024)
Cancer is a serious illness that experienced by children. In Indonesia, less than 30% of children cancers can be treated, due mostly to the parents' lack of awareness about care for child cancer patients, that includes therapy, medication, and nutritional therapy specifically for treatment of cancer. Father has responsibility in caring family’s health, including caring children with nutritional problem due to of illness. Objective: In this study, we reviewed literatures related to the father’s role and or father’s support in fulfilling children’s nutrition need during cancer treatment. Method: In this study, out of 1540 studies from the PubMed, Wiley, Science Direct, and Google Scholars, 7 articles included in the study analysis. The articles explored about fathers’ role and involvement in nutrition management with the children cancer patients (<18 yrs old) were included. Review, study reports, and articles related to the nutrition management in adult cancer patients have been excluded. Results: Majority articles showed a helpful connection between support and fathers' roles in children's nutrition to promote recovery and therapy development for pediatric cancer patients. Two themes emerged from the study; (1) Father’s Role in Recognizing the Nutrition Problems related to the Cancer (2) Father’s Support in Fulfilling Nutrition. Conclusion: Fathers' support for their children's cancer might improve their quality of life. The rigid relationship between children and fathers may also enhance children's appetite, increasing the chances of curing cancer in children.